Hemosiderotic dermatofibroma mimicking melanoma: A case report and review of the literature - Changzhao Li; Hunter Allen; Margarita Loxas; Poonam Sharma (Clinical Case Reports, 2021)
Abstract Hemosiderotic dermatofibroma (HDF) often mimics melanoma clinically. A definite diagnosis relies on histopathological evaluation and immunohistochemistry. As it can progress to aneurysmal dermatofibroma (ADF), complete excision is recommended.